Faktor-Faktor yang Mempengaruhi Minat Menggunakan E-Zakat dalam Membayar Zakat, Infaq, dan Sedekah - Puguh Kharisma; Prabowo Yudo Jayanto (AKSES: Jurnal Ekonomi dan Bisnis, 2021)
In the modern era like today, it also changes the model of financial transactions that were previously carried out conventionally, now it can be done digitally or online using financial technology. This digital transaction trend has also changed the payment methods for Zakat, Infaq, and Alms that were previously done conventionally, now it can be done digitally through the E-Zakat service provided by the Zakat Management Organization. In the last 5 years, there has been a significant trend of increasing digital payments of Zakat, Infaq, and Almsgiving. This has become a new phenomenon in collecting Zakat, Infaq, and Alms funds so that what factors also influence the interest of muzaki to use E-Zakat in paying Zakat, Infaq, and Alms so that there is a trend of increasing the intensity of digital ZIS payments needs to be known so that the collection Zakat, Infaq and Alms funds can be maximized. The population of this research is amil who work at OPZ at provincial and national scale in Semarang City who have opened E-Zakat service. The sampling technique used was quota sampling and the number of samples was 70 respondents. Primary data collection using a questionnaire method. Data were analyzed using descriptive analysis and Structural Equation Modeling (SEM) with the SmartPLS 3.0 analysis tool. The results show that Usability and Transparency have a significant positive effect, Risk has a significant negative effect on Interests in Using E-Zakat, but Accountability has no significant effect on Interests in Using E-Zakat in Paying Zakat, Infaq, and Alms. Based on the research results, it can be concluded that the interest in using E-Zakat in paying Zakat, Infaq, and Alms is influenced by the Usability, Risk and Transparency variables of the E-Zakat service. The suggestions from researchers for OPZ are expected to be able to maintain and improve the quality of service and add features for muzaki / donors. For further researchers, it is hoped that they can develop research by examining other factors that are thought to influence the interest in using E-Zakat in paying Zakat, Infaq, and Alms. It is expected to present the ease of use variable to complement the variable elements in the Technology Acceptance Model (TAM) theory. Keywords: E-Zakat, Zakat Management Organization, Management, Digital Transactions, ZIS, Online